Bcl-2 expression in circulating tumor cells (CTCs) of patients with small cell lung cancer (SCLC) receiving front-line treatment. (October 2018) - Messaritakis, Ippokratis; Nikolaou, Michail; Politaki, Eleni; Koinis, Fillipos; Lagoudaki, Eleni; Koutsopoulos, Anastasios; Georgoulia, Nefeli; Georgoulias, Vassilis; Kotsakis, Athanasios
Highlights: Presence of Bcl-2 + CTCs in chemotherapy-naïve SCLC patients. Cinical relevance during front-line treatment. Important phenotypic CTCs heterogeneity. Abstract: Introduction: To investigate the presence of Bcl-2 + CTCs in chemotherapy-naïve SCLC patients and their clinical relevance during front-line treatment. Methods: Peripheral blood was obtained from 66 consecutive-patients before chemotherapy administration, after one-cycle and at relapse. CTCs were detected by CellSearch and immunofluorescence using anti-Bcl-2, anti-M30, anti-cytokeratins(CK), anti-CD45 and anti-vimentin(Vim) antibodies. Results: Before treatment, CTCs were detected in 62.1% and 72.7% of patients using the CellSearch and immunofluorescence (Bcl-2 + /CD45 − ), respectively. One-treatment cycle significantly decreased both CTCs' detection rate( p < 0.001) and their absolute number ( p < 0.001). On relapse, both the number of positive-patients and the absolute number of CTC subpopulations were significantly increased, compared to post-1st cycle (CellSearch: p = 0.002 and immunofluorescence: p < 0.001). Immunofluorescence revealed an important CTC heterogeneity (Bcl2 + /Vim +, Bcl2 + /Vim −, Bcl2 + /CK +, Bcl2 + /CK − and Bcl2 + /M30 − CTCs). Moreover, 50.0% of patients without detectable CTCs by CellSearch had detectable Bcl-2 + /CD45 − cells. Multivariate analysis revealed a significant association between Bcl-2 + /CD45 − cells at baseline and PFS (HR = 4.5; p = 0.005) and OS (HR: 4.3; p = 0.001). Bcl-2 + /CD45 − cells after one-treatment cycle were significantly associated with shorter OS (HR: 13.9; p = 0.007). Conclusions: These results demonstrate an important phenotypic CTCs heterogeneity based on the co-expression of Bcl-2, CK, Vim and M30 in SCLC patients. The changes of Bcl-2 + /CD45 − CTCs during treatment seem to be a dynamic biomarker associated with treatment efficacy and patients' clinical outcome.